Fatores associados à distribuição espacial dos homicídios em Belo Horizonte - Gabriela Gomes Cardoso (2015)
The criminal fiel of study dedicated to verify the distribution of crimes space has become increasingly important in academic works. The relationship between structural features and play criminal pattern that is present has become increasingly central this study. The ecological studies, porcelain by Chicago school, points to a residential mobility ethnic heterogeneity and economic deprivation, forms factors of social disorganization in the communities, hurting formal and informal control capability that places. But the association arrangements between the structural characteristics and criminal occurrences are poorly explored. Another research group seeks to explain the formations and influence of criminal groups or drug traffickres over the territories. Studies like of savenije and friends(2007) they point out that the formation of these groups is more likely in places marked by social exclusion. Therefore, this paper seeks to interact these two theoretical groups, believing that the formation of the fifty-two drug traffickers groups can be applied to homicide concentrations in certain places in town. In special we investigated the spatial distribution pattern of the muders and drug trafficking in the city of Belo Horizonte, indentifying these types of criminal are concentrated in specific locations. Situational analysis ecological unit of census tracts and has build an indicator of social disorganization of communities to evaluate their effect on homicide rates in these areas. And then sought to analyze the same relationship mediated by drug trafficking charges. In noted that both the indicator of social disorganization as drug trafficking rates are positively associated with the homicide occurrences It was also noticed that part of the effect of clutter on homicides through the drug trade but direct effect is more expressive. Furthermore, the effect of traffic on the homicides was more intense. Therefore, it concludes drug trafficking is more relevant in explaining the spatial concentration patterns of homicides